2020
DOI: 10.1002/jhet.3818
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐based benzoxazines synthesized in a deep eutectic solvent: A greener approach toward vesicular nanosystems

Abstract: A green synthesis of benzoxazines, based upon reaction of cardanol with formaldehyde and primary amines, is achieved in high yields using choline chloride-urea mixture as deep eutectic solvent. Then, it is demonstrated how the cardanol-based benxoxazines can be employed as only component for the preparation of a nanovesicular systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…More eco‐friendly CuAAC procedures rely on either the use of water as the reaction medium under heterogeneous conditions [10] or the employment of biodegradable, environmentally responsible, nature‐inspired Deep Eutectic Solvents (DESs) [11] under homogeneous [12] or heterogeneous [13] conditions. Building upon our recent findings on the preparation of enolates [14] and variously functionalized nitrogen heterocycles (e. g., pyrazines, imidazoles, pyrimidines, 2‐aminoimidazoles, 2‐pyrazinones, benzoxazines) [15–19] directly in DESs, in this work we demonstrate the versatility of type III eutectic mixtures (formed by an ammonium salt and an hydrogen bond donor) in enabling transition‐metal‐free cycloaddition reactions between enolates of alkanones and azides to afford densely functionalized 1,2,3‐triazoles (Scheme 1c).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…More eco‐friendly CuAAC procedures rely on either the use of water as the reaction medium under heterogeneous conditions [10] or the employment of biodegradable, environmentally responsible, nature‐inspired Deep Eutectic Solvents (DESs) [11] under homogeneous [12] or heterogeneous [13] conditions. Building upon our recent findings on the preparation of enolates [14] and variously functionalized nitrogen heterocycles (e. g., pyrazines, imidazoles, pyrimidines, 2‐aminoimidazoles, 2‐pyrazinones, benzoxazines) [15–19] directly in DESs, in this work we demonstrate the versatility of type III eutectic mixtures (formed by an ammonium salt and an hydrogen bond donor) in enabling transition‐metal‐free cycloaddition reactions between enolates of alkanones and azides to afford densely functionalized 1,2,3‐triazoles (Scheme 1c).…”
Section: Introductionmentioning
confidence: 61%
“…[9] More eco-friendly CuAAC procedures rely on either the use of water as the reaction medium under heterogeneous conditions [10] or the employment of biodegradable, environmentally responsible, nature-inspired Deep Eutectic Solvents (DESs) [11] under homogeneous [12] or heterogeneous [13] conditions. Building upon our recent findings on the preparation of enolates [14] and variously functionalized nitrogen heterocycles (e. g., pyrazines, imidazoles, pyrimidines, 2-aminoimidazoles, 2pyrazinones, benzoxazines) [15][16][17][18][19] directly in DESs, in this work we Notable features of our report include i) reactions run under mild conditions (room temperature), ii) broad substrate scope (26 examples) and high regioselectivity, with the desired educts prepared in good to excellent yields (up to 98 %), iii) ability to telescope enolate formation/click cycloaddition/reduction or etherification reactions in a one-pot process to synthesize valuable pharmacologically active triazole derivatives.…”
Section: Introductionmentioning
confidence: 97%
“…Behalo et al developed a green Mannich-like condensation of a cardanol with its unsaturated derivative, aniline, and formaldehyde, in ChCl/urea as DES with good yields (81–88%) ( Scheme 5 ). They also demonstrated the use of cardanol-based benzoxazines as scaffolds for the preparation of vesicular nanosystems [ 57 ].…”
Section: Choline-based Des As Solvents/catalysts In Pharmaceutical Synthesismentioning
confidence: 99%
“…In addition, some different synthesis strategies for the preparation of these compounds continue to be developed. Multicomponent synthesis of bio‐based benzoxazines from cardanol by using a deep eutectic solvent [ 30 ] and a modified method based on arylboronic acids has also been described. [ 31 ] Vengatesan et al reported ultrasound‐assisted synthesis of benzoxazine monomers.…”
Section: Introductionmentioning
confidence: 99%